RELEVANSI BELANJA ONLINE TERHADAP PERILAKU KONSUMTIF MASYARAKAT: Studi Kasus Kp. Sembung 1, Desa Gunungsembung Kec. Pagaden Subang - Ainul Haq; Irvan Iswandi (Melati Institute, 2022)
The more people who have the Online Shopping platform, the convenience and motivation of people's shopping increases as well. This makes many people who make online shopping an alternative, some make it their main media for shopping, some even just make it a side job by opening stalls through the online shopping platform. This study aims to find out how the positive legal review and Islamic law regarding the relevance of buying and selling online to the consumptive behavior of the community in Kp. Sembung 1, Gunungsembung Village, Kec. Pagaden Subang. With the above problems, the specific goal is to find out how far the relationship between the consumptive behavior of the community and the existence of online shopping activities is related to positive law and Islamic law. This study used qualitative research methods. The data used are primary data, data collection by documentation and interview methods. Primary data sources in this study were obtained through iforman, namely people who are used to shopping online. Regarding secondary data sources used in the form of documents, books, notes, and so on. The results of this study indicate that 1) Online shopping with consumptive behavior is very sustainable, because consumptive behavior will not occur without opportunities that make it easier for buyers to get the goods they want easily, so they are often unconscious to buy goods that are less or even the same. absolutely not needed. So there is a very close relationship or relevance between online shopping and consumptive behavior, especially for some people in Kp. Sembung 1 Rt 02 Rw 01 Village. Gunungsembung District. Pagaden Subang Regency. An overview of Islamic law on online shopping in Kp. Sembung 1 Rt 02 Rw 01 Village. Gunungsembung District. Pagaden Subang Regency that there are no elements that violate Islamic law. Contracts in online buying and selling transactions are different from direct contracts. Electronic transactions usually use a written contract. Buying and selling through electronic media is a sale and purchase transaction carried out using modern technology, the validity of which depends on whether or not the pillars or conditions that apply in the sale and purchase are fulfilled. While the terms of the seller and buyer are reasonable. Then in the sale and purchase contract, the agreement and acceptance have been made, the ownership of the goods changes hands from the seller's hands to the buyer's hands and the value of money changes vice versa.